Hasil dan Komponen Hasil Beberapa Varietas Kacang Hijau (Vigna radiata L. Wilczek) yang Diberi Pemupukan Kieserit: Hasil dan Komponen Hasil Beberapa Varietas Kacang Hijau (Vigna radiata L. Wilczek) yang Diberi Pemupukan Kieserit - Buhaira; Nusifera, Sosiawan; Salim, Helmi (Universitas Bangka Belitung, 2024)
Mungbean is one of food plants that has important role as a source of nutrition. One of the important macronutrient elements which its deficiency can disrupt the photosynthesis process resulting in reduced mungbean growth and yield is Mg (magnesium). Research aimed to determine responses of several varieties to application of different doses of kieserite fertilizer and to obtain the best dose for each varieties. Experiment was arranged in a randomized block design (RBD) with a two-factor factorial pattern. The first factor was four varieties i.e. ‘Vima 1’, ‘Vima 3’, ‘Vima 5’, and ‘Vimil 1’. Second factor was four levels of kieserit fertilizer dosage (0, 50, 100, and 150 kg ha-1). Observed variables were yield and yield components. Data were analyzed using analysis of variance and Duncan's test at 5% α level. Results showed that the responses of four varieties used were relatively the same to the dose of kieserit, and dose aplication of kieserit 50 kg.ha-1 could increase yield. Highest yielding variety was Vima-5 variety with highest number of pods and yield per plant. While the lowest yielding variety was Vimil-1 variety which had lower seed size (weight 100 seeds) than of other varieties.